(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Anastatus tenuipes Bolivar y Pieltain, 1925 (Hymenoptera, Eupelmidae), parasitoid of oothecae of Supella longipalpa (F.) (Blattaria, Blattellidae) is newly reported for Italy and Europe. Main data on diagnostic characters, biology and distribution of the species are given.